Զ.—Թ. դարերի հայ հոգեւոր դասի կերպավորումը Հովհաննես Դրասխանակերտցու Պատմության մէջ - Ավագյան, Վաչագան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье исследуются образы почти всех духовных деятелей, о которых упоминает в своей «Истории Армении» известный армянский Католикос, историк X века Ованес Драсханакертци. Духовные деятели жили в VI—IX веках и удостоились внимания историка своей деятельностью. Выявляя их сословные и личные качества, автор статьи также указывает принципы и приемы создания историком каждого образа, частоту использования этих принципов в разнообразии изображения раскрывает сходства и различия образов. The article studies images of almost all religious figures portrayed in the “History of Armenia” by the famous Armenian Catholicos, historian of the 10th century Hovhannes of Draskhanakert. They lived from the 6th to the 9th centuries and became worthy of the attention of the historian for their works. Revealing their class and personal qualities, the author of the article also indicates the principles and techniques for creating each character, the frequency of their use, thus revealing the similarities and differences of characters in the variety of images.
Keywords: Հայոց պատմություն; Կրոնագիտություն